A novel theatre-based behaviour change approach for influencing community uptake of schistosomiasis control measures - Sule, May N.; Mosha, Justina; Soboka, Teshome Emana; Kinung’hi, Safari M.; Sfynia, Chrysoula; Rafiq, Kamran; Dower, Alex; Comparet, Marianne; Bewley, Emma; Angelo, Teckla; Beshah, Feleke Zewge; Templeton, Michael R. (BMC - Springer, 2022)
Background: Appropriate behaviour change with regard to safe water contact practices will facilitate the elimination of schistosomiasis as a public health concern. Various approaches to effecting this change have been trialled in the field but with limited sustainable outcomes. Our case study assessed the effectiveness of a novel theatre-based behaviour change technique (BCT), in combination with cohort awareness raising and capacity training intervention workshops. Methodology: Our study was carried out in Mwanza, Tanzania and Kemise, Ethiopia. We adapted the Risk, Attitude, Norms, Ability, and Self-regulation (RANAS) framework and four phases using a mixed methods approach. Participatory project phase engagement an11 qualitative formative data were used to guide the design of an acceptable, holistic intervention. Initial baseline (BL) data was collected using quantitative questionnaire surveys with 804 participants in Tanzania and 617 in Ethiopia, followed by the theatre-based BCT and capacity training intervention workshops. Post-intervention (PI) survey was carried out after six months, with a participant return rate of 65% in Tanzania and 60% in Ethiopia. Results: The intervention achieved a significant improvement in the knowledge of schistosomiasis transmission being associated with poorly managed sanitation and risky water contact. Participants in Tanzania increased their uptake of preventive chemotherapy (Male: BL:56%; PI:73%, Female: BL:43%; PI:50%). There was a significant increase in the selection of sanitation (Tanzania: BL:13%; PI:21%, Ethiopia: BL:63%; PI:90%), safe water and avoiding/minimising contact with infested waters as prevention methods in Tanzania and Ethiopia. Some of the participants in Tanzania followed on from the study by building their own latrines. Conclusions: This study showed substantial positive behaviour changes in schistosomiasis control can be achieved using theatre-based BCT intervention and disease awareness training. With appropriate sensitisation, education and stakeholder engagement approaches, community members were more open to minimising risk-associated contact with contaminated water sources and were mobilised to implement preventive measures.
Keywords: Schistosomiasis; Water; Sanitation; WASH; Behaviour change; Theatre; Role-play